2022
DOI: 10.1186/s40623-022-01734-y
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric responses on the 21 August 2017 solar eclipse by using three-dimensional GNSS tomography

Abstract: In this study, we have investigated the ionospheric responses on the August 2017 solar eclipse event by using a three-dimensional tomography algorithm with the ground-based GNSS (Global Navigation Satellite System) total electron content observations around Northern America. This three-dimensional ionospheric electron density structure from the tomography can provide us more information regarding the density variations and propagations of disturbances. Results show that the ionospheric electron density depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…These profiles reveal a noticeable Ne reduction of 3-7 × 10 11 el/m 3 (∼30%-50%) across the bottomside and topside ionosphere, which occurred shortly after the onset of the local eclipse, reaching the largest depletion in the ionospheric F2 region between 250 and 350 km approximately 30-40 min after the local maximum obscuration. The reduction in Ne exhibits an altitude-dependent feature, with a more pronounced depletion observed around the ionospheric F2-layer peak region, which is consistent with that of 2017 Great American solar eclipse as observed by incoherent scatter radar (Goncharenko et al, 2018) or reconstructed using tomography technique (C. H. Chen et al, 2022). Specifically, the maximum Ne reduction was 5.7 × 10 11 el/m 3 (∼44%) at ∼260 km over Pt Arguello, 6.5 × 10 11 el/m 3 (∼46%) at ∼280 km over Boulder, 6.8 × 10 11 el/m 3 (∼42%) at ∼300 km over Austin, and 5.9 × 10 11 el/m 3 (∼35%) at ∼300 km over Eglin.…”
Section: -D Ionospheric Electron Density Variationssupporting
confidence: 77%
See 1 more Smart Citation
“…These profiles reveal a noticeable Ne reduction of 3-7 × 10 11 el/m 3 (∼30%-50%) across the bottomside and topside ionosphere, which occurred shortly after the onset of the local eclipse, reaching the largest depletion in the ionospheric F2 region between 250 and 350 km approximately 30-40 min after the local maximum obscuration. The reduction in Ne exhibits an altitude-dependent feature, with a more pronounced depletion observed around the ionospheric F2-layer peak region, which is consistent with that of 2017 Great American solar eclipse as observed by incoherent scatter radar (Goncharenko et al, 2018) or reconstructed using tomography technique (C. H. Chen et al, 2022). Specifically, the maximum Ne reduction was 5.7 × 10 11 el/m 3 (∼44%) at ∼260 km over Pt Arguello, 6.5 × 10 11 el/m 3 (∼46%) at ∼280 km over Boulder, 6.8 × 10 11 el/m 3 (∼42%) at ∼300 km over Austin, and 5.9 × 10 11 el/m 3 (∼35%) at ∼300 km over Eglin.…”
Section: -D Ionospheric Electron Density Variationssupporting
confidence: 77%
“…By examining the 3-D variations in ionospheric electron density, we can enhance the comprehension of the multi-dimensional alterations in the ionosphere during an eclipse, thereby advancing the current understanding of the mechanisms that drive these changes (Aa, Forsythe, et al, 2023). Recently, some pioneering works have been conducted to reconstruct the 3-D ionospheric structure during the eclipse utilizing data assimilation or tomography technique C. H. Chen et al, 2022;He et al, 2018;Lin et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, some previous studies indicate that the 2-D TEC depletion was up to 50% (e.g., [30]) and the ionospheric F-region peak electron density decrease was around 30-50% (e.g., [10,35,36]). In addition, the tomography results given by Chen et al [46] showed a maximum Ne depletion of 40%. In comparison to these prior investigations, the altitude-resolved measurements from MHISR clearly demonstrate that the Ne depletion could be more substantial around regions of totality, reaching levels of 50-60% around 200-300 km as illustrated in Figure 1e.…”
Section: Mhisr and Ionosonde Resultsmentioning
confidence: 84%
“…They reported that the maximum Ne depletion occurred around 200 km. Chen et al [46] also employed a three-dimensional tomography algorithm with ground-based GNSS TEC observations to build the ionospheric Ne structures. They found that the maximum Ne depletion was around ∼40% compared to the previous day.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that electron density decreases when the altitude increases, and the TEC data reduced to 20-40% during the SE. Chen et al [7] did an extensive analysis on the TEC changes in the August 2017 SE happened over the North America region based on a 3D tomography algorithm. Te results show that 40% electron density depletion occurred as compared to the previous day.…”
Section: Introductionmentioning
confidence: 99%